Prevalence of classic and non-classic antiphospholipid antibodies in multiple sclerosis (2015)
Background: The association between antiphospholipid antibodies (aPL) and multiple sclerosis (MS) has been suggested previously, but prior studies provided contradicting findings. Objectives: To characterize the expression profile of eight classic and non-classic aPL in patients diagnosed with MS. Methods: Using the BioPlex™ 2200 immunoassay, we measured the levels of serum immunoglobulin (Ig)M and IgG isotypes of three classic aPL and five non-classic aPL in 98 subjects with MS and 237 healthy controls. Results: Three non-classic aPL were significantly more prevalent among MS patients in comparison to the control group. These antibodies included IgM and IgG against phosphatidylserine- ?2GPI (PS-B2), IgG prothrombin complex (PT-PT) and IgM prothrombin (PT). The positive results according to Bonferroni correction are PS-B2 IgG and PT-PT IgG. The remaining aPL profiles did not differ significantly between the two groups. Conclusions: An association between certain non-classic aPL and MS has been established. The specific role of these autoantibodies in the pathogenesis of the condition remains uncertain. © 2015, Israel Medical Association. All rights reserved.